Integration of TQM, Malcolm Baldrige, and EFQM for Quality Improvement in Satellite Madrasahs - Meika Findi Nikensi; Nabila Luthfia Syaharoh; Fetty Ernawati; Shahzadi Hina (Mapendis: Jurnal Manajemen Pendidikan Islam, 2026)
Improving educational quality requires a management system capable of integrating a quality culture, data-driven evaluation, leadership, and continuous improvement, particularly in madrasah filial (satellite Islamic schools) facing resource constraints. This study aims to analyze the integration of Total Quality Management (TQM), the Malcolm Baldrige framework, and the European Foundation for Quality Management (EFQM) model in enhancing educational quality within these schools. A qualitative approach was employed, utilizing descriptive research and a case study design. Data were gathered through semi-structured interviews, observations, and document analysis involving purposively selected school principals, teachers, educational staff, and students. Data analysis followed the interactive model proposed by Miles, Huberman, and Saldaña, comprising data condensation, data display, and conclusion drawing and verification. The results indicate that the integration of these three approaches occurred adaptively: TQM served as the primary orientation for quality culture; the Malcolm Baldrige framework strengthened evaluation and data-driven decision-making (via SKP and e-Kinerja systems); and the EFQM model reinforced leadership, collaboration, and human resource development. This integration was realized by focusing on student needs, stakeholder engagement, the development of academic and non-academic programs, and continuous improvement. The findings demonstrate that quality enhancement in madrasah filial is not solely determined by resource availability but also by the organization's ability to optimize resources through leadership, collaboration, evidence-based evaluation, and continuous improvement. This study contributes to the field of Islamic educational quality management by showing that principles from various quality models can be integrated contextually. Future research is encouraged to utilize multi-site, comparative, longitudinal, or mixed-methods studies to examine the maturity level of this model integration and its impact on educational outcomes.